Evaluation of anti-cancer potential of Excoecaria agallocha (L.) leaf extract on human cervical cancer (SiHa) cell line and assessing the underlying mechanism of action - Tamanna Sultana; Arup Kumar Mitra; Satadal Das (SpringerOpen, 2022)
Abstract Background The incidence of cervical cancer is increasing at an alarming rate in many countries and presently, it is the most common form of malignant cancer being reported among women in India. Development of novel approach for cervical cancer therapy, sparing healthy normal cells overcoming the limitations of prevailing therapies is of prime importance. Mangroves constitute a significant repository of medicinally important plants. Thus, in this study, we aimed to determine the anticancer activity of the mangrove Excoecaria agallocha L. leaf extracts on human cervical cancer (SiHa HPV 16+) cell line with subsequent characterization of the bioactive compounds conferring the anticancer activity and studying the probable underlying mechanism of action of the purified plant extract. Results The plant extract was subjected to silica gel column chromatography and the fractions obtained were analyzed for cytotoxic activity against SiHa cells by MTT assay. One out of the three eluted fractions exhibited selective toxicity against SiHa cells with an IC50 value of 15.538 ± 0.577 µg/mL, while it had no cytotoxic effect on normal healthy human peripheral blood mononuclear cells. High-resolution liquid chromatography mass spectroscopy, coupled to electron spray ionization and diode array detection analysis, led to the structure elucidation and identification of a few pharmacologically important compounds, with Bergenin being present in the highest abundance. Fluorescence microscopy results revealed that the plant extract fraction induced LC3 puncta formation, in EGFP- SiHa cells indicating the onset of autophagy, with simultaneous stimulation of mitophagy. The plant extract also inhibited proliferation of the SiHa-smac-mCherry cells by second mitochondria-derived activator of caspase (SMAC)-induced cytochrome c dependent apoptosis, that was further confirmed with Caspase-3 activation by colorimetric assay. The GFP-dgn in SiHa cells was remarkably protected from proteasomal degradation that might upregulate the survivability of the cells significantly. Flow cytometry followed by Western blot analysis further asserted the ability of the plant extract fraction to cause cell cycle arrest of SiHa cells in the G2/M phase by significantly reducing protein expression levels of cyclin B1 and D1, decreasing Cdc2 level and simultaneously increasing p21 and p53 levels. Conclusion It could be inferred that the aqueous extract of E. agallocha successfully decreased the proliferation of SiHa cervical cancer cells through induction of autophagy and apoptosis in a concerted manner, with simultaneous stimulation of mitophagy and G2/M phase cell cycle arrest, hinting at Bergenin being the major compound conferring the anti-cancer activity of the plant extract. Thus, isolation of the identified bioactive compounds from E. agallocha and their subsequent purification for drug development might serve as a novel medicinal approach for the treatment of cervical cancer in conjugation with existing therapeutic methods.